2020
DOI: 10.1016/j.jhin.2020.01.005
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for Klebsiella pneumoniae carbapenemase (KPC) gene acquisition and clinical outcomes across multiple bacterial species

Abstract: Introduction: Risk factors for carbapenemase-producing Enterobacterales (CPE) acquisition/ infection and associated clinical outcomes have been evaluated in the context of clonal, species-specific outbreaks. Equivalent analyses for complex, multi-species outbreaks, which are increasingly common, are lacking. Methods: Between December 2010 and January 2017, a caseecontrol study of Klebsiella pneumoniae carbapenemase (KPC)-producing organism (KPCO) acquisition was undertaken using electronic health records from … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
17
0
4

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 36 publications
4
17
0
4
Order By: Relevance
“…On univariate analysis, as in previous studies, [9][10][11]17,[21][22][23] we found that risk factors for both CP-CRE colonization and non-CP-CRE colonization included nursing home residency before hospital admission, antibiotic treatment 3 months before admission, urinary catheter, decubitus ulcer, and mechanical ventilation. We did not find men to be at an increased risk for CP-CRE or non-CP-CRE colonization in comparison to other studies, 9,10 which may have been due to an older patient population in our study and the longer life expectancy of women in Israel.…”
Section: Discussionsupporting
confidence: 77%
See 3 more Smart Citations
“…On univariate analysis, as in previous studies, [9][10][11]17,[21][22][23] we found that risk factors for both CP-CRE colonization and non-CP-CRE colonization included nursing home residency before hospital admission, antibiotic treatment 3 months before admission, urinary catheter, decubitus ulcer, and mechanical ventilation. We did not find men to be at an increased risk for CP-CRE or non-CP-CRE colonization in comparison to other studies, 9,10 which may have been due to an older patient population in our study and the longer life expectancy of women in Israel.…”
Section: Discussionsupporting
confidence: 77%
“…CRE resistance can be divided into 2 major groups: CP-CRE and non-CP-CRE. Previous studies [9][10][11][12][17][18][19][20][21][22][23][24] have addressed the issue of risk factors for CRE colonization/infection as a whole (ie, 1 group), showing that the following factors were associated with CRE acquisition: male sex, nursing home residency before hospital admission, history of admission within 1 year, poor functional status, Charlson index score ≥3, urinary catheter, decubitus ulcer, mechanical ventilation, intensive care unit stay, undergoing an invasive procedure with a scope device, and prior antibiotic exposure including penicillins, cephalosporins, carbapenems, vancomycin and fluoroquinolones.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This phenomenon also contributes to the global spread of Carbapenemase-producing bacteria becoming therefore especially worrisome [20]. It has been shown that Enterobacterales spp., such as Escherichia coli and Klebsiella pneumoniae, are common human pathogens and asymptomatic colonizers of the human gastrointestinal tract and environmental niches [21]. Our study reported for the rst time the occurrence of Carbapenemase-producing E. coli and Salmonella in children with diarrhea in rural settings of Burkina Faso.…”
Section: Discussionmentioning
confidence: 69%